2015
DOI: 10.1111/hir.12095
|View full text |Cite
|
Sign up to set email alerts
|

Medical scientists' information practices in the research work context

Abstract: Information practices appear as an instrument producing activity to the central activity. Information services should be embedded in this core activity and in practice libraries should follow researchers' workflow and embed their tools and services in it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this study, we have reanalyzed data, which was collected during the years 2007 and 2012 (earlier results reported by Roos et al , 2008; Roos, 2012, 2015). In the 2008 article, the analysis focussed on the quantitative part of the data, while in the 2012 and 2015 articles the activity theoretical research frame was used in the analyses and based on data collected from interviews and observations.…”
Section: Methods and Research Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have reanalyzed data, which was collected during the years 2007 and 2012 (earlier results reported by Roos et al , 2008; Roos, 2012, 2015). In the 2008 article, the analysis focussed on the quantitative part of the data, while in the 2012 and 2015 articles the activity theoretical research frame was used in the analyses and based on data collected from interviews and observations.…”
Section: Methods and Research Settingsmentioning
confidence: 99%
“…In total, 95 percent of MM researchers and all medical scientists in our studies were using it. Information is searched from PubMed in a very simple way, often like laymen use the general search engines (Roos et al , 2008; Roos, 2015).…”
Section: Information Practices In Biomedicinementioning
confidence: 99%
“…They reported that information practices of nurses are "corporeal (sentient and sensory) information practices related to seeing, hearing, touching and smell which form the 'gut instincts'" (p. 1,219). In his study of the information practices of medical officers, Roos (2015) proposed a 12-stage model of the information practices of medical scientists that related each information practice to a specific goal in their research process. These practices focus on retrieving, evaluating and sharing of information.…”
Section: Literature Survey 21 Prior Research On Information Practicesmentioning
confidence: 99%
“…Information practice is at the forefront of our minds in this issue of the Health Information and Libraries Journal starting with a qualitative study of the medical scientists working in a research context. Using semistructured interviews, Roos uses activity theory to develop an understanding of medical scientist researchers' information related practice and notes that the characteristics of the researchers discipline need to be understood and taken into account when providing information support. Her findings indicate that a key element of developing this share understanding is the need to develop a common language for discussions about information related services, thereby increasing the perceived relevance of library and information services within the research community.…”
Section: In This Issue…mentioning
confidence: 99%
“…In the United Kingdom, we have a role in supporting our international colleagues, particularly those in developing countries, to continue to develop as a profession, and for them to nurture influence with senior management in their own organisations and at broader governmental level. This editorial provides an overview of a range of organisations working to improve access to health information in developing countries including Book Aid International, 1 HIFA, 2 INASP, 3 ITOCA, 4 Phi, 5 TALC, 6 THET 7 and Research4Life. 8 Saving lives through health information is the vision of Partnerships in Health Information (Phi), a charitable organisation working in partnership with African health librarians and others to improve access to accurate, relevant and up-to-date evidence for health professionals and the public in Sub-Saharan Africa.…”
mentioning
confidence: 99%